2019
DOI: 10.1016/j.addbeh.2018.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking rates among veterans: Association with rurality and psychiatric disorders

Abstract: Aims: Compared to the general U.S. population, military veterans and those living in rural areas disproportionately smoke cigarettes at higher rates, leading to increased health consequences. In the current study, prevalence and severity of cigarette smoking in Iraq and Afghanistan era veterans was assessed across rural and urban areas and comorbid mental health disorders. Method: Iraq/Afghanistan era veterans who participated in the Post-Deployment Mental Health study from 2005-2017 (N = 3229) were cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…People in rural and remote areas might experience more problems in accessing and following advice that is relevant to prevention [17], and often have lower educational attainment, poorer health literacy, experience more food insecurity, and have poorer or a higher cost to access healthy foods [18][19][20]. The rates of smoking are higher in rural areas and in people experiencing stress or mental illness [21,22], and the use of services that support quitting smoking has been found to be lower in rural residents [23]. There is a known higher prevalence of risk factors, such as rates of alcohol consumption and obesity in rural Australia [24].…”
Section: Preventionmentioning
confidence: 99%
“…People in rural and remote areas might experience more problems in accessing and following advice that is relevant to prevention [17], and often have lower educational attainment, poorer health literacy, experience more food insecurity, and have poorer or a higher cost to access healthy foods [18][19][20]. The rates of smoking are higher in rural areas and in people experiencing stress or mental illness [21,22], and the use of services that support quitting smoking has been found to be lower in rural residents [23]. There is a known higher prevalence of risk factors, such as rates of alcohol consumption and obesity in rural Australia [24].…”
Section: Preventionmentioning
confidence: 99%
“…Recent critiques have argued that studies reporting an inverse correlation between smoking and testing positive have several methodological flaws, such as not having smoking as the primary exposure, low prevalence of smokers in cohorts, lacking explicit data on smoking status, not adjusting for confounders associated with smoking, and unexpectedly low percentages of chronic obstructive pulmonary disease and cardiovascular disease particularly among smokers, indicating potential selection bias [ 45 , 46 ]. Veterans are known to use tobacco products at a higher rate than non-veterans [ 47 , 48 , 49 ]. According to a 2016 report, 32.5% of veterans who served after 2001 are Current Smokers, 24.8% are Former Smokers, and 42.7% are Never Smokers [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a study on tobacco users derived from psychiatric and primary care units in São Paulo, Brazil, it was found that those of male sex and those with PDs were more likely to have greater tobacco dependence 35 . In addition, a study among US veterans demonstrated that those with PDs living in extremely rural areas were more tobacco dependent compared to their urban counterparts without PDs 13 . The scant information on the relationship between different demographic factors and tobacco consumption among rural and urban psychiatric patients necessitates that more studies be conducted to better understand and help this at‐risk population.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, a study among US veterans demonstrated that those with PDs living in extremely rural areas were more tobacco dependent compared to their urban counterparts without PDs. 13 The scant information on the relationship between different demographic factors and tobacco consumption among rural and urban psychiatric patients necessitates that more studies be conducted to better understand and help this at-risk population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation